Study on the Evaluation Method of Transmission Gear Rattle Noise based on Energy Fluctuation - Gao Siqi; Ding Weiping; Yang Mingliang; Wang Shoujian; Su Ruiqiang; Shen Chao (Jixie chuandong)
The gear rattle noise is analyzed from the perspective of energy fluctuation and a metric named"energy fluctuation metric"is proposed for the evaluation of gear rattle. A transmission system dynamics model is established with ADAMS software and "energy fluctuation metric"is used to analyze transmission gear rattle noise. The simulation analysis is compared with experiment test data and subject evaluation. In addition,the gear rattle threshold is determined. It is found that "energy fluctuation metric"has a good effect on evaluating gear rattle noise and it could be used to improve transmission performance.